Effect of grinding adjustments on the color of monolithic zirconia - Corcodel, Nicoleta; Herpel, Christopher; Seceleanu, Irina; Rion, Kevin; Hassel, Alexander J.; Rammelsberg, Peter (The journal of prosthetic dentistry, 2022)
Monolithic zirconia restorations have become popular because of their excellent mechanical properties and acceptable esthetics. While the biomechanical properties of zirconia have been investigated, research into their esthetic properties is sparse. Zirconia can be colored by infiltration before sintering, although how occlusal adjustment can affect restoration color is unclear. The purpose of this in vitro study was to analyze the color of differently characterized monolithic white and precolored zirconia specimens after standardized grinding.